Bienestar psicológico en estudiantes de la carrera de medicina de la Universidad Nacional de Loja - Neira Guerrero, Darío Vicente (2022)
Psychologic welfare (BP) is the way of living that leads people to feel satisfied with themselves and implies the development of potentialities and strengths. Extensive research suggests that a high prevalence of stress in physicians often originates in medical school, even during the preclinical years. For this reason, a quantitative, observational prospective crosssectional study was developed, with the objective of determining academic performance and its relationship with psychological welfare in students of the UNL Medicine career. A total of 131 students participated in the study, 70.23% (n=92) of students were female and 29.77% (n=39) were male; 66.41% (n=87) are between 21 and 25 years old, 25.96% (n=34) belong to the range of 17 to 20 years old and 7.63% (n=10) are between the ages of 26 to 30 years old. 74.05% (n=97) of the students presented a High BP, of these 33.59% (n=44) belong to the female sex and 14.50 (n=19) to the male sex with a range aged 21 to 25 years; 17.05% (n=23) had a Moderate BP and 3.82% (n=5) had a Low BP. 70.99% (n=93) of the students presented a Good Academic Performance (RA); 28.24% (n=37) had a Very Good AR and 0.76% (n=1) had a Low AR. A p value of 0.114 was obtained, showing that there is no statistically significant relationship between Psychologic welfare and Academic Performance